ROLE OF LOCAL INFILTRATION OF INJECTION BUPIVACAINE IN REDUCING EARLY POST-OPERATIVE PAIN - Mudassar jabeen; Fawad Zafar; Sumara Tabassam; Farhad Alam; Muhammad Sohail (Journal of University Medical & Dental College, 2020)
ABSTRACT: BACKGROUND & OBJECTIVE: Intolerable morbidity occurs after major thoracic, orthopedic or abdominal surgeries due to post-operative pain. Inadequately controlled pain leads to patient displeasure and major morbidities like postoperative pulmonary dysfunctions and cardiac ischemic changes. Various techniques are presently used to treat this pain and opiods are the most regularly used medications by parenteral or neuraxial route. Intolerable morbidity occurs post-operatively due to inadequately controlled pain. The objective of this study was to compare the mean pain scores in patients undergoing laparotomy with and without local inﬁltration of injection bupivacaine at surgical incision site in post-operative period. METHODOLOGY: This randomized controlled trial was conducted at surgical department Allied hospital Faisalabad from June 2017 to December 2017.Total 80 patient were included in this study that were randomly divided into two groups using random number tables. In post-operative period, patients of both groups were given treatment as per requirement of their respective diseases. They received a baseline analgesia using Inj. Toradol (ketorolac) 30mg/1ml intravenously every 8 hours, ﬁrst dose given during the surgery. The study group was additionally given 10ml Inj. Bupivacaine HCl 0.5% diluted with 10ml saline injected into the subcutaneous plane around the incision immediately after the closure of skin and time was noted. No further diﬀerence in the treatment of patients of both groups required for the purpose of this study. The patients in both groups were compared for the degree of pain experienced by them in early post-operative period. This information was collected using Numeric pain scale, 10 being worst pain and 1 meaning least appreciable pain. These assessments were done 2 and 4 hours after surgery. RESULTS: We recorded pain score 3.0+0.75 in study and 5.2+0.72 in control group, p-value was < 0.001 showing a signiﬁcant diﬀerence. CONCLUSION: We concluded that there is signiﬁcantly lower pain in patients inﬁltrated with injection bupivacaine around surgical incision in early post-operative period as compared to those who had only intravenous analgesics.